Methylation of PRDX3 Expression Alleviate Ferroptosis and Oxidative Stress in Patients with Osteoarthritis Cartilage Injury - Xia Zhao; Yixue Peng; Mengsong Wang; Qishuang Tan (Archives of Rheumatology, 2025)
Background/Aims: Osteoarthritis features cartilage degeneration, synovial fibrosis, and bone remodeling. Long-term Western therapies may worsen cartilage damage. We investigated PRDX3’s role in ferroptosis and oxidative stress in osteoarthritis cartilage injury. Materials and Methods: In osteoarthritis models, PRDX3 expression was downregulated. Single-cell analysis showed PRDX3 in patient bone cells. Results: Sh-PRDX3 promoted cartilage injury via oxidative stress induction. PRDX3 suppressed ROS accumulation and mitochondria-dependent ferroptosis in vitro and mouse models. PRDX3 induced SIRT3 to reduce SIRT3 ubiquitination. METTL3-mediated m6A modification decreased PRDX3 mRNA stability via YTHDF1. Conclusion: METTL3-mediated m6A decreases PRDX3 mRNA stability to relieve ferroptosis and oxidative stress in osteoarthritis models. Targeting METTL3 may be therapeutic.